(3GdEJaGbjI GdYGeI ddJLGQI aj GdNOeGJ (B(GATS) (3hYdGbJgG HbWGY Gdfbd aj GdOhd GdYQHjI (B/s - (3dGTjf, YHO GdbGOQ aJMj s ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2005)
(3GdJLGQI GdNGQLjI hGdfXGe GdJLGQj GdOhdj GdLOjO(B- (3GdJLGQI GdOhdjI aj GdNOeGJ Ydi NQjWI GdEbJUGO GdYGdej(B- (3efXeI GdJLGQI GdYGdejI hGdfXGe GdJLGQj GdOhdj GdLOjO(B- (3GdEfVeGe Gdi efXeI GdJLGQI GdYGdejI hehba GdEdJReGJ ddOhd GdefXeI MOjKG(B- (3GdEJaGbjI GdYGeI ddJLGQI aj GdNOeGJ(B((3GdLGJS(B)- (3GdJLGQI aj GdNOeGJ LGJS (B2000- (3ehba GdEdJReGJ GdebOeI ddJLGQI GdNGQLjI(B- (3GdBKGQ GdeJhbYI dEJaGbjI Ydi bWGY Gdfbd hGdEWGQ GdYed GdebJQM(B- (3GdNdGUI hGdJhUjGJs
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdOhdjIs; (3GdbGfhf GdOhdj GdJLGQjs; (3efXeI GdJLGQI GdYGdejI (BGATSs